Influence of the reaction between water and ZnO on the properties of Au Schottky contacts and the photocatalytic activity of ZnO(0001) single crystals - Koji Abe (Materials Research Express, 2022)
Wet chemical treatment is a conventional surface cleaning method, and metal oxide photocatalysts are commonly used to decompose organic compounds in water. In this study, we have investigated the influence of the reaction between water and ZnO on the properties of Au Schottky contacts and the photocatalytic activity of Zn-face ZnO(0001) single crystals. The ZnO substrate was put in deionized water at temperatures between 40 °C and 90 °C (water treatment). The ZnO substrate was etched with deionized water, and the surface roughness increased with increasing water temperature. Although the water treatment had no significant influence on the surface composition of the ZnO substrate, it changed the properties of the Au contacts. Schottky contacts were formed on the as-received ZnO substrate and the ZnO substrate after the water treatment at 40 °C, whereas ohmic contacts were formed on the ZnO substrate after the water treatment at 90 °C. Photoelectron emission spectra showed that the surface Fermi level in the ZnO substrate after the water treatment at 90 °C was located just below the conduction band. However, the water treatment had no significant influence on the photocatalytic activity of the ZnO substrate. Even when the water treatment was performed at 90 °C, the surface Fermi level of the ZnO substrate in an electrolyte solution, which was estimated from photoelectrochemical measurements, was located about 0.4 eV below the conduction band.